Habenular expression of rare missense variants of the β4 nicotinic receptor subunit alters nicotine consumption - Ślimak, Marta A.; Ables, Jessica L.; Frahm, Silke; Antolin-Fontes, Beatriz; Santos-Torres, Julio; Moretti, Milena; Gotti, Cecilia; Ibañez-Tallon, Ines (Frontiers in Human Neuroscience, 2014)
The CHRNA5-CHRNA3-CHRNB4 gene cluster, encoding the α5, α3, and β4 nicotinic acetylcholine receptor (nAChR) subunits, has been linked to nicotine dependence. The habenulo-interpeduncular (Hb-IPN) tract is particularly enriched in α3β4 nAChRs. We recently showed that modulation of these receptors in the medial habenula (MHb) in mice altered nicotine consumption. Given that β4 is rate-limiting for receptor activity and that single nucleotide polymorphisms (SNPs) in CHRNB4 have been linked to altered risk of nicotine dependence in humans, we were interested in determining the contribution of allelic variants of β4 to nicotine receptor activity in the MHb. We screened for missense SNPs that had allele frequencies >0.0005 and introduced the corresponding substitutions in Chrnb4. Fourteen variants were analyzed by co-expression with α3. We found that β4A90I and β4T374I variants, previously shown to associate with reduced risk of smoking, and an additional variant β4D447Y, significantly increased nicotine-evoked current amplitudes, while β4R348C, the mutation most frequently encountered in sporadic amyotrophic lateral sclerosis (sALS), showed reduced nicotine currents. We employed lentiviruses to express β4 or β4 variants in the MHb. Immunoprecipitation studies confirmed that β4 lentiviral-mediated expression leads to specific upregulation of α3β4 but not β2 nAChRs in the Mhb. Mice injected with the β4-containing virus showed pronounced aversion to nicotine as previously observed in transgenic Tabac mice overexpressing Chrnb4 at endogenous sites including the MHb. Habenular expression of the β4 gain-of-function allele T374I also resulted in strong aversion, while transduction with the β4 loss-of function allele R348C failed to induce nicotine aversion. Altogether, these data confirm the critical role of habenular β4 in nicotine consumption, and identify specific SNPs in CHRNB4 that modify nicotine-elicited currents and alter nicotine consumption in mice.